(Post-)Colonial Business History and the Coloniality of the Firm: The Case of the Woermann Group, 1884-1945 - Kim Sebastian Todzi (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2025)
By providing a working definition of an expatriate colonial business, this article examines the role of the Woermann group's integration into and support of colonialism through trade, plantations, and logistics. Focusing on its activities in Cameroon and the pivotal role of the Woermann Linie during the Herero and Nama genocide in German South West Africa, it illustrates the company's entanglement with German colonial rule. Even after the end of Germany's colonial overseas empire, colonial influences persisted in the company's structure and practices, emphasizing the enduring impact of coloniality on business operations.
Keywords: N47; N73; N77; N83; N87; 330; colonialism; business; trade; shipping; Cameroon; Namibia; genocide; capitalism; German colonialism